Analysis of Shopee Application-Based Digital Marketing Strategy for Cokelat Mojopahit CV. Bayu Dewa Brahma, Mojokerto Regency - Pranindhita, Anggie Nur; Widayanti, Sri; Hendrarini, Hamidah (Universitas Muhammadiyah Pontianak, 2025)
This study analyzes the Shopee application-based digital marketing strategy of the MSME Cokelat Mojopahit CV. Bayu Dewa Brahma, Mojokerto Regency. The objective is to formulate effective strategies to increase sales and brand awareness. The SOSTAC method was applied, covering situation analysis, objectives, strategy, tactics, action, and control. Data were collected through interviews, observation, documentation, and literature review. Results show a 30% sales increase and 50% growth in social media followers after implementing digital promotion, Shopee Live, and micro-influencer collaboration. The findings highlight digital channel optimization, content innovation, and strategic partnerships as key steps to strengthen MSME competitiveness in an increasingly competitive online market.